Implementation of the Rapid Application Development (RAD) method for guidance and counseling: a case study at SMPN 3 Pakuhaji - Yulianto, Muhammad Arief; Khoirunnisya, Khoirunnisya (Jurnal Ilmiah Teknologi Informasi Asia, 2026)
This study presents the development and evaluation of a web-based Guidance and Counseling Information System at SMPN 3 Pakuhaji using the Rapid Application Development (RAD) method. Prior to system implementation, counseling services relied on manual documentation and face-to-face reporting, resulting in delayed case processing, limited monitoring, and inefficient data management. The RAD approach was applied through iterative prototyping cycles involving continuous feedback from counselors and teachers to ensure alignment with user requirements. The system was developed using PHP and MySQL, supported by UML modeling and database design. System evaluation was conducted using black-box testing to verify functional correctness and performance measurement to assess operational efficiency. The results indicate that counseling case processing time was reduced from approximately 2–3 working days to 3–5 hours, representing an efficiency improvement of about 85%. In addition, a user satisfaction survey involving 45 respondents yielded a 84.1% score, categorized as “Strongly Agree.” These findings demonstrate that the RAD-based system effectively improves the efficiency, accuracy, and accessibility of counseling services. The study confirms that iterative user-centered development not only accelerates system delivery but also enhances system usability and practical effectiveness in educational counseling environments.